The archaeology of religion - Steadman, Sharon R., author.
1 online resource (xxi, 435 pages)
Keywords: "The new and updated edition of Archaeology of Religion explores how archaeology interprets past religions, offering insights into how archaeologists seek out the religious, ritual, and symbolic meaning behind what they discover in their research. The book includes case studies from around the world, from the study of Upper Palaeolithic and hunter-gatherer religions to religious structures and practices in complex societies of the Americas, Mesopotamia, Egypt, India, and China. Steadman also includes chapters on the origins and development of key contemporary religions-Judaism, Christianity, Islam, among others-to provide an historical and comparative context. Three main themes are threaded throughout the book. These main themes involve the intersection between cultural and religious structures ("religion reflects culture"), including the importance of environment in shaping a culture's religion, the role religion can sometimes play as a method of social control, and the role religion can sometimes play as a key component in revitalizing a culture. Updated with new discoveries and theories and with two new chapters (Hunter-Gatherer Religions, and Cultures in East Asia), and with new sections on Neolithic Western Asia, the book remains an ideal introduction for courses that include a significant component on past cultures and their religions"--